Effects of feedback control on chaotic convection in fluid-saturated porous media - Roslan, R.; Mahmud, M. N.; Hashim, I. (Elsevier, 2011)
Thermal convective instability in a fluid-saturated porous layer heated from below and cooled from above is investigated theoretically using dynamical systems approach. A feedback control strategy with an array of sensors situated at the top plate of the fluid layer is adopted. The Galerkin truncated approximation is employed to derive a low dimensional Lorenz-like model. It is shown that suppression or enhancement of chaotic convection is possible via feedback control.